Does quality time produce quality children? Evidence on the intergenerational transmission of human capital using parental deaths - Eric D. Gould; Avi Simhon (Institute for the Study of Labor (IZA), 2011)
This paper uses variation created by parental deaths in the amount of time children spend with each parent to examine whether the parent-child correlation in schooling outcomes stems from a causal relationship. Using a large sample of Israeli children who lost one parent during childhood, we find a series of striking patterns which show that the relationship is largely causal. Relative to children who did not lose a parent, the education of the deceased parent is less important in determining child outcomes, while the education of the surviving parent becomes a stronger factor. Moreover, within the group of families that lost a parent, this pattern intensifies when a child loses a parent earlier in life - the education of the deceased parent becomes even less important, while the effect of the surviving parent's schooling intensifies. These results provide strong evidence that there is a causal connection between parent and child schooling, which is dependent on the child's interaction time with each parent. These findings help us understand why educated parents typically spend more time with their children - they are more effective in producing human capital in their children.
urn:nbn:de:101:1-201104113600
Keywords: I21; J13; J24; 330; intergenerational mobility; education; Kinder; Bildungsniveau; Familiensoziologie; Generationenbeziehungen; Humankapital; Alleinerziehende; Schätzung; Israel